Case Report: Interventional therapy for portal venous stenosis caused by systemic vasculitis - Cai, Qiuyu; Wei, Bo; Tai, Yang; Wu, Hao (Frontiers in Immunology, 2022)
Systemic vasculitis are multisystem blood vessel disorders. However, Portal venous involvement is extremely rare, which represents a diagnostic and therapeutic challenge due to the heterogeneous nature, a lack of diagnostic criteria and limited effective therapy of vasculitis. We have reported a 48-year-old woman who was previously diagnosed with system vasculitis and was treated with prednisone, presented with gastrointestinal (GI) bleeding on admission. Further abdominal contrast-enhanced computed tomography (CT) with three-dimensional reconstruction suggested atrophic left hepatic lobe, enlarged spleen, and severe stenosis of main portal vein. Liver biopsy showed no evidence of fibrosis/cirrhosis. To prevent rebleeding, portal venous angioplasty by balloon dilation with collateral varices embolization was performed, and the GI hemorrhage was resolved completely. However, refractory ascites presented 8 months postoperatively. Abdominal CT angiography confirmed the recurrence of portal venous stenosis. Portal venous angioplasty by stent implantation was then performed to treat the portal hypertension (PHT)-related complications. After the intervention, the patient received anticoagulation therapy and continued immunosuppressive therapy. During the 5-year follow-up, the patient did not experience any onset of GI bleeding or ascites. Therefore, portal venous angioplasty with stent placement could be an effective treatment to prevent PHT-related complications when immunosuppression therapy failed.